2022
DOI: 10.1007/s40265-021-01670-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel Agents for the Pharmacological Treatment of Alcohol Use Disorder

Abstract: Alcohol use disorder (AUD) is a highly prevalent but severely under-treated disorder, with only three widely-approved pharmacotherapies. Given that AUD is a very heterogeneous disorder, it is unlikely that one single medication will be effective for all individuals with an AUD. As such, there is a need to develop new, more effective, and diverse pharmacological treatment options for AUD with the hopes of increasing utilization and improving care. In this qualitative literature review, we discuss the efficacy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 314 publications
(340 reference statements)
0
62
0
Order By: Relevance
“…Importantly, α-synuclein is highly expressed in the excitatory synapses marked by vesicular glutamate transporter-1 [ 53 , 54 ] and believed to be involved in mobilization of glutamate from the reserve pool [ 55 ]. Since glutamate plays a principle role in alcohol seeking, alcohol addiction and relapse [ 56 , 57 , 58 ] and chronic alcohol treatment promotes abnormal synaptic transmission that may lead to hippocampal cell death resulted from glutamate excitotoxicity after ethanol withdrawal [ 59 ]. Taking into account that α-synuclein knockout mice have cognitive impairments [ 60 ] we can suggest that the identified effect of downregulation of α-synuclein mRNA in HPC, perhaps, may be partly responsible for cognitive deficit which is typical for PAE offspring [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, α-synuclein is highly expressed in the excitatory synapses marked by vesicular glutamate transporter-1 [ 53 , 54 ] and believed to be involved in mobilization of glutamate from the reserve pool [ 55 ]. Since glutamate plays a principle role in alcohol seeking, alcohol addiction and relapse [ 56 , 57 , 58 ] and chronic alcohol treatment promotes abnormal synaptic transmission that may lead to hippocampal cell death resulted from glutamate excitotoxicity after ethanol withdrawal [ 59 ]. Taking into account that α-synuclein knockout mice have cognitive impairments [ 60 ] we can suggest that the identified effect of downregulation of α-synuclein mRNA in HPC, perhaps, may be partly responsible for cognitive deficit which is typical for PAE offspring [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in detail above, several different drugs and medication classes have been investigated for their potential use in the treatment of alcohol use disorder, a clinical area where there is a desperate need for new treatment strategies ( Burnette et al, 2022 ). Some have shown very promising results, while others have not proven useful.…”
Section: Summary Interpretation and Outlookmentioning
confidence: 99%
“…All patients with known AP should receive abstinence counseling [43]. A randomized controlled trial showed that abstinence counseling during AP reduced the recurrence rate of AP over 2 years [44].…”
Section: Alcohol Cessationmentioning
confidence: 99%